Effect of Transplanting Age and Spacing System on Growth and Yield of Glutinous Rice (Oryza sativa L.var glutinosa) Grendel Variety - Hamdani, Hamdani; Komariah, Ai; Mulyana, Hudaya (Institute of Computer Science (IOCS), 2023)
The research was conducted in the paddy fields of the Nanjung Tani farmer group, Rawameneng Village, Blanakan District, Subang Regency, at a height of 25 m above sea level, from August 2022 to November 2022. This research aimed to study the effect of the interaction between the spacing system and the age at which the garden was moved on the growth and yield of glutinous rice. latch. The environmental design used a completely randomized design (CRD) with a factorial pattern, the plant spacing treatment (j) consisted of 3 levels, namely j1 = Legowo 2 ; 1, j2 = 30 cm x 30 cm tiles, j3 = 4:1 thinning and the age of transplanting (u) consists of 4 levels, namely u1 = 10 HSS, u2 = 15 HSS, u3 = 20 HSS and u4 = 25 HSS . The results showed that the effect of transplanting age and spacing had an interaction effect on the number of tillers and the number of productive tillers, whereas on plant height, wet sample weight, dry sample weight, 1000 grain weight, empty grain weight, panicle length , number of seeds per panicle and tiles showed no interaction